Return to play for athletes after COVID-19 infection. The fog begins to clear - Udelson, J. E.; Rowin, E. J.; Maron, B. J. (JAMA Cardiology, 2021)
In October 2020, Kim and colleagues, representing the American College of Cardiology`s Sports and Exercise Council, published recommendations1 for the evaluation of athletes who had tested positive for COVID-19 to ensure safe return to play. The group recommended a tiered approach based on the presence of symptoms, followed by electrocardiography (ECG), injury biomarkers, and echocardiography. Abnormalities were then to be further characterized by the selective use of cardiac magnetic resonance (CMR) imaging. The recommendations were based on expert opinion of experienced sports cardiologists, because there were at the time only modest data to inform such a document. A report2 on 26 college athletes who were asymptomatic or had only mild symptoms found CMR evidence of myocarditis in 4 (15%). Both the Kim et al report1 and our Editorial3 at the time called for larger data sets, so that recommendations could be refined and more informed by data.